Hadith Of Commandment Killing Snakes In The Book Of Sunan Abu Daud: Textual And Contextual Understanding - Miftahul Khaira; Afdilla Nisa (Institut Agama Islam Sumatera Barat, 2024)
This study aims to understand the hadith concerning the command to kill snakes and to enhance knowledge and comprehension for practical application in daily life. Snakes, as legless reptiles with elongated, scaly bodies, play a crucial role in the food chain. Prophet Muhammad SAW once instructed Al-Abbas ibn Abdul Muthalib to kill small snakes in the Zamzam well and emphasized in another hadith that not killing them would mean not being part of the Prophet's community. This research employs a qualitative library research method, utilizing primary and secondary sources, with primary reference to the Kitab Sunan Abi Dawud. The hadiths were collected through takhrij and analyzed both textually and contextually. The analysis results indicate that textually, Rasulullah commanded to kill all types of snakes, especially those in the house after being warned for three days. However, contextually, only venomous snakes that pose a threat and danger should be killed to prevent extinction, considering the important role of snakes in controlling the population of other animals.